A Solitary Malignant Schwannoma in the Choana and Nasal Septum - Eun Jung Lee; Kee Jae Song; Yeon Suk Seo; Kyung-Su Kim (Case Reports in Otolaryngology)
Malignant schwannoma is an extremely rare tumor and the risk of malignant schwannoma increases in patients with von Recklinghausen’s disease. Recently, we encountered a case of solitary malignant schwannoma in the choana and posterior nasal septum. Malignant schwannoma has not been previously reported in these locations. A 53-year-old man, who was immunologically healthy and showed no abnormal dermatological lesions, presented with a polypoid mass in the right nasal cavity and underwent endoscopic mass excision. The mass originated from the choana and the posterior portion of the right nasal septum. This mass was confirmed as a malignant schwannoma on histological examination and immunohistochemical staining. After endoscopic excision, postoperative adjuvant radiotherapy was administered, and there was no recurrence at 1 year after treatment. This case suggests that a solitary malignant schwannoma should be considered in the differential diagnosis of a mass in the posterior nasal cavity.